Analisis Soal Ujian Biologi Tipe Higher Order Thinking Skill Berbasis Daring Selama Masa Pandemi Covid 19 Sekolah Menengah Atas - Mohammad Mulyadi Prasetyo; Nurhidayah Nurhidayah (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
This research is a descriptive study where data is collected with the aim of knowing the characteristics and obtaining information about the Higher Order Thinking Skill (HOTS) type of Final Exam questions. The subject of this research is the Biology Final Semester Examination for the 2020/202 Academic Year. This research has two stages, namely: Preparation and implementation stage to obtain documents in the form of school exam questions. Research data were collected through: (1) Problem Analysis, Researchers, biology education lecturers, and biology teachers analyzed each question from 3 characteristics that were fulfilled in each item, namely indicators consisting of stimulus, critical thinking skills, and solving abilities. problem. (2). Carry out FGD (Focus Group Discussion) to determine whether each item is included in the type of stimulus, critical thinking ability, and problem solving ability. (3) Tabulate the data for the results of the analysis of each question number. then the results of the analysis are tabulated on each indicator. The results obtained in this study are almost all HOTS type questions (95%), on the characteristics of almost all items (94.2%) in accordance with the provisions of competency achievement indicators. On the stimulus indicator, all HOTS type questions have a stimulus. Where "half" of the HOTS questions is stimulated by pictures, "less than half" is stimulated by case fragments and a small portion is stimulated by diagrams, tables, and examples. In critical thinking indicators, 91.86% of the "almost all" categories of HOTS questions have critical thinking characteristics, in addition that "a small part" (26.23%) of HOTS questions have problem solving characteristics including problem solving questions with indicators of identifying problems, identifying non-conforming problems, and solving problems based on data.